Sistemas de Información para el Control de Transferencia en una Cadena de Manufactura - Torres Acosta, Jairo Humberto (Ingeniería, 2008)
The activity of transference of the physical current of units in a manufacture chain, it requires for its monitoring and control a robust information system. This it must consist of an entrance subsystem, whose components are information of exit of other preceding systems; an operational subsystem, to determine the different behaviors of interest between the different processes of the manufacturing chain and exit subsystem that it allows with its results of establishing the monitoring and control. A chain of manufacture by processes, it is a complex system and the control of transference of its physical current of units and it requires an information system of high complexity. The development of this article generates the structure of the operational information system for the control of transference of a chain of manufacture by processes.